2017
DOI: 10.4103/0019-5154.198031
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis and risk of celiac disease: A systematic review and meta-analysis

Abstract: Background and Objectives:The possible association between psoriasis and celiac disease (CD) has long been observed, but epidemiologic studies attempting to characterize this association have yielded inconclusive results. This meta-analysis was conducted with the aims to summarize all available data.Methods:We conducted a systematic review and meta-analysis of observational studies that reported relative risk, hazard ratio, odds ratio (OR), or standardized incidence ratio with 95% confidence interval (CI) comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 20 publications
0
29
0
3
Order By: Relevance
“…There are some evidences to suggest that B and T cells that recognize epitopes presented on gluten proteins can sometimes have cross‐reactivity to self‐antigens . This explanation may also explain why patients with celiac diseases have a higher risk of developing several autoimmune diseases, not only sarcoidosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some evidences to suggest that B and T cells that recognize epitopes presented on gluten proteins can sometimes have cross‐reactivity to self‐antigens . This explanation may also explain why patients with celiac diseases have a higher risk of developing several autoimmune diseases, not only sarcoidosis.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 In addition, studies have demonstrated that these patients are at an increased risk of developing several comorbidities including such as psoriasis, chronic kidney disease and venous thromboembolism. [8][9][10][11][12] Sarcoidosis is a multisystemic granulomatous disease of unknown etiology characterized by the formation of noncaseating granuloma c 2019 Chinese Cochrane Center, West China Hospital of Sichuan University and John Wiley & Sons Australia, Ltd in the involved organs. 13 It commonly affects the lungs and intrathoracic lymph node but can virtually affect any organs.…”
Section: Introductionmentioning
confidence: 99%
“…Coeliac disease is an immune‐mediated enteropathy characterized clinically by malabsorption and histologically by villous atrophy and crypt hyperplasia. In a meta‐analysis, the risk of coeliac disease has been shown to be increased in patients with psoriasis . However, HLA‐Cw6 was not associated with coeliac disease‐associated antibodies in patients with psoriasis …”
Section: Association With Other Comorbiditiesmentioning
confidence: 99%
“…States and approximately 125 million people worldwide [81]. Ps is considered to be a multifactorial disease, in which the genetic background interacts with environmental factors to define the individual's risk [82]. The classical clinical manifestations of Ps consist in the presence of red, infiltrated plaques, covered with a coarse silvery scaling (Figures 14,15).…”
Section: Psoriasismentioning
confidence: 99%
“…For many years, the relationship between Ps and CD remained controversial since the few available data were inconclusive. A recent meta-analysis has demonstrated a significantly higher risk of CD among patients with psoriasis compared with participants without psoriasis with the OR of 3.09 (95%CI= 1.92-4.97) [82]. Furthermore, there are seven studies that have reported a positive association between psoriasis and CD markers [85][86][87][88][89][90][91][92].…”
Section: Psoriasismentioning
confidence: 99%